Reinterpretasi Ayat Kebebasan Beragama Dalam Konteks Kontemporer: Antara Teks Dan Realitas - Muhammad Afdhal (Yayasan Nanggroe Aceh Mulia, 2026)
The issue of religious freedom is a crucial theme in contemporary Islamic discourse, particularly amidst the dynamics of pluralistic and complex modern society. Debates often arise between textual understandings of Quranic verses and social realities that demand respect for individual religious freedom. The background to this research stems from the tension between some classical interpretations, which tend to be normative, and the contextual needs of today's society. This research aims to reanalyze (reinterpret) the verses on religious freedom in the Quran, taking into account the historical and social contexts, as well as the development of contemporary thought. Furthermore, this research aims to bridge the gap between text (nash) and reality (waqi') to achieve a more relevant and applicable understanding. The research method used is a qualitative method with a thematic interpretation (maudhu'i) approach. Data were collected through library research, referring to classical and contemporary interpretation books, as well as supporting literature related to the issue of religious freedom. The research findings indicate that verses on religious freedom, such as the principle of